SIRT 2.0: Smart interactive revision tool - Mazrul, Muhammad Ashrul Hardy; Safien, Muhammad Aiman; Zainal, Muhammd Faiz; Mohd Mydin, Azlina; Wan Mohammad, Wan Anisha (2022)
Smart Interactive Revision Tool (SIRT 2.0) is a new approach to perform revision in an interesting up to current situation that align to STEM education. This approach allows the student from all levels of education either from school or university student to enjoy their revision duration. Students face problems while doing revision such as they will feel bored to do revision. SIRT 2.0 allows the student to create their own revision notes and example interestingly in video form using TikTok. This SIRT 2.0 is the upgrade version from the 1st edition with additional features. SIRT 2.0 is designed especially for Pre-Comm students for subject MAT 037. Student can create short video notes on the topic from the syllabus according to their understanding. A survey has been done to know the satisfaction about SIRT 2.0 among the Pre-Comm students from UiTM Cawangan Pulau Pinang. Around 60 students were involved in the survey. From the survey, almost everyone satisfied and enjoy doing revision using SIRT 2.0. They also liked the style of the videos in SIRT 2.0 that could help them in doing revision through notes and examples for the MAT 037 subject. SIRT 2.0